2022
DOI: 10.1088/1755-1315/956/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of flavonoid content and antioxidant activity in calyces of two roselle varieties (Hibiscus sabdariffa L.)

Abstract: Free radicals can cause various degenerative diseases such as cancer and cardiovascular disease. Flavonoids have antioxidant abilities that inhibit damage from free radicals. The roselle antioxidant mechanism is associated with high flavonoid content. Red and purple roselles are two varieties of roselle (Hibiscus sabdariffa L.) cultivated in Indonesia. The aim of this research was to analyze the differences in flavonoid content and antioxidant activity in the calyces of two varieties of roselle (Hibiscus sabda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Penelitian oleh Adrianto (2019), menunjukkan aktivitas antioksidan ekstrak etanol 70% dan 96% bunga rosella berturut-turut memiliki nilai IC50 sebesar 17,57 ppm dan 15,236 ppm. Penelitian oleh Nerdy et al (2022), ekstrak etanol bunga rosella memiliki nilai IC50 sebesar 51,59 μg/mL. Penelitian oleh Shafirany et al (2021), ekstrak bunga rosella memiliki nilai IC50 sebesar 63,77 μg/mL.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Penelitian oleh Adrianto (2019), menunjukkan aktivitas antioksidan ekstrak etanol 70% dan 96% bunga rosella berturut-turut memiliki nilai IC50 sebesar 17,57 ppm dan 15,236 ppm. Penelitian oleh Nerdy et al (2022), ekstrak etanol bunga rosella memiliki nilai IC50 sebesar 51,59 μg/mL. Penelitian oleh Shafirany et al (2021), ekstrak bunga rosella memiliki nilai IC50 sebesar 63,77 μg/mL.…”
Section: Pendahuluanunclassified
“…Antioksidan merupakan senyawa non-reaktif dan stabil yang dapat mendonorkan satu atau lebih elektron kepada radikal bebas. Sehingga, antioksidan dapat mengurangi atau menetralkan efek berbahaya dari radikal bebas (Nerdy et al, 2022). Bunga rosella dapat menjadi salah satu alternatif alami sebagai antioksidan .…”
Section: Pendahuluanunclassified
“…The seeds are kidney-shaped, light brown, and up to 5 mm long [ 2 , 7 , 8 ]. The flower calyces are usually red (rose), but there are also white and purple varieties [ 8 , 9 ].…”
Section: Hibiscus Sabdariffa —Characteristicmentioning
confidence: 99%
“…The white variety is characterized by a higher ability to scavenge free radicals than the red variety [ 8 ]. Another study demonstrated that purple calyces exhibit stronger antioxidative activity and contain more flavonoids than red ones [ 9 ]. However, most studies are conducted on the active compounds of the red variety.…”
Section: Hibiscus Sabdariffa —Characteristicmentioning
confidence: 99%